Survey on gynecological cancer treatment by Piedmont, Liguria, and Valle d’Aosta group of AIRO (Italian Association of Radiation Oncology) - Cattari, Gabriella; Delmastro, Elena; Bresciani, Sara; Gribaudo, Sergio; Melano, Antonella; Giannelli, Flavio; Tessa, Maria; Chiarlone, Renato; Scolaro, Tindaro; Krengli, Marco; Urgesi, Alessandro; Gabriele, Pietro (Journal of Contemporary Brachytherapy, 2016)
Purpose : We focused the attention on radiation therapy practices about the gynecological malignancies in Piedmont, Liguria, and Valle d’Aosta to know the current treatment practice and to improve the quality of care. Material and methods : We proposed a cognitive survey to evaluate the standard practice patterns for gynecological cancer management, adopted from 2012 to 2014 by radiotherapy (RT) centers with a large amount of gynecological cancer cases. There were three topics: 1. Taking care and multidisciplinary approach 2. Radiotherapy treatment and brachytherapy, 3. Follow-up. Results : Nineteen centers treated gynecological malignancies and 12 of these had a multidisciplinary dedicated team. Radiotherapy option has been used in all clinical setting: definitive, adjuvant, and palliative. In general, 1978 patients were treated. There were 834 brachytherapy (BRT) treatments. The fusion between diagnostic imaging (magnetic resonance imaging – MRI, positron emission tomography – PET) and computed tomography (CT) simulation was used for contouring in all centers. Conformal RT and intensity modulated radiation therapy (IMRT) were the most frequent techniques. The image guided radiation therapy (IGRT) was used in 10/19 centers. There were 8 active BRT centers. Brachytherapy was performed both with radical intent and as boost, mostly by HDR (6/8 centers). The doses for exclusive BRT were between 20 to 30 Gy. The doses for BRT boost were between 10 and 20 Gy. Four centers used CT-MRI compatible applicators but only one used MRI for planning. The BRT plans on vaginal cuff were still performed on traditional radiographies in 2 centers. The plan sum was evaluated in only 1 center. Only 1 center performed in vivo dosimetry. Conclusions : In the last three years, multidisciplinary approach, contouring, treatment techniques, doses, and control systems were similar in Liguria-Piedmont and Valle d’Aosta. However, the technology implementation didn’t translate in a real treatment innovation so far.